SISTEM INFORMASI GEOGRAFIS KEPENDUDUKAN PADA KANTOR DESA LAMBUR LUAR KABUPATEN TANJUNG JABUNG TIMUR - simorangkir, lucy (FORTECH (Journal of Information Technology), 2017)
Abstrak - Desa Lambur Luar Office is a government institution that serves the community in various needs. One of them is data collection of population, death data, birth data, and processing in the form of monthly report. In the data processing there is still information that can be accessed by data, which amounts altogether, because the number of heads of household in one house, so when the population data is often error, besides the data processing of population in Desa Lambur Luar also still using manual system, the data is still stored in the books agenda. To overcome these problems then needed a web-based information system applications so that data does not have a long time in search data, and easily find information that live in every home residents and the location of each homes residence by determining the cobalt point that can be seen through google maps. Can be able to produce a fast, precise, and accurate information and provide ease of information.                                          Keywords: Information System, Data Population, Geographic, Website